CARBONATE RESERVOIR STUDY BATURAJA FORMATION, RAYU BLOCK, SOUTH SUMATRA BASIN - TIFANI , DWIMARA
Blok Rayu lies on Musi platform in southern part of South Palembang Sub Basin. Tectonic settings this region was bordered by Palembang depression in the northen part, Pigi through in the western part, Benakat Gulley in the eastern part and Gumai mountain in the southern part. Wireline logs analysis of 8 wells in study area utilized gamma ray log, rho (density) and neutron for detecting distribution of carbonate Baturaja Formation. Seismic facies analysis generate distribution of lateral facies association. This results divide Baturaja Formation of three zones. Wireline log and thin section data role as validator of analysis lateral distributions. Integration of seismic facies and electrofacies exhibit carbonate depositional pattern dominated by build up under lithofacies coral w-p and skeletal w-p. Depositional pattern fine grained (muddy) encountered on mudstone with facies association platform interior. Reservoir characterization involve comprehension about depositional facies as well as property of reservoir rocks existed. This study will learn reservoir characterization from Baturaja Formation, on Rayu Field which is part of South Sumatra Sub Basin. Study include depositional facies and pattern distribution of reservoir rock properties. Data used for this study consists of thin sections and description results from two wells, wireline log, consist of gamma ray, density and neutron logs and seismic also rock properties consist of effective porosity and permeability. Study this field be expected reservoir heterogeneity Baturaja Formation can be represented and understood subsequently build geological modeling from distribution of facies association resulting consistent interpretation from facies distribution depositional environments thus effective porosity-permeability which is a reflection of the depositional environment.